2015
DOI: 10.5455/aim.2015.23.202-205
|View full text |Cite
|
Sign up to set email alerts
|

Family Medicine Education with Virtual Patients: a Qualitative Study

Abstract: Objectives:Virtual patients (VP) have been present within the medical education process for some time. Although they are assumed to be of great benefit for student learning, very little is know about student perception and outcomes of learning, especially during the pre-clerkship years. Therefore we have decided to investigate the use of VPs during lectures, which has never been analyzed before, but could present an opportunity for more effective and holistic learning.Methods:This was a qualitative study among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…The identified four dimensions were about knowledge acquisition, management of learning, the impersonal nature of learning and other disadvantages of learning. The identified dimensions are similar to our expectations, based on the defined literature review and other available literature reviews (Edelbring et al, , ; Huwendiek et al, ; Sobocan & Klemenc‐Ketis, ). The factors presented in the available literature strengthened our case for the reliability of the VPIRS scale.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The identified four dimensions were about knowledge acquisition, management of learning, the impersonal nature of learning and other disadvantages of learning. The identified dimensions are similar to our expectations, based on the defined literature review and other available literature reviews (Edelbring et al, , ; Huwendiek et al, ; Sobocan & Klemenc‐Ketis, ). The factors presented in the available literature strengthened our case for the reliability of the VPIRS scale.…”
Section: Discussionsupporting
confidence: 88%
“…The factors presented in the available literature strengthened our case for the reliability of the VPIRS scale. Previous research on VPs, especially in a medical school environment, noted that the advantages of integrating VPs as part of course duties include a flexible work environment as well as knowledge reorganization by students and their appreciation of immediate feedback (Edelbring et al, 2011;Sobocan & Klemenc-Ketis, 2015;Sullivan, Bingman, O'Rourke, & Pugh, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Students used the VP repository MedU for internal medicine. In previous studies, students highly favoured the use of MedU repositories for undergraduate education . Immediately after the intervention (a 4‐week module), students took the gastroenterology knowledge exam and the Diagnostic Thinking Inventory (DTI) measurement.…”
Section: Methodsmentioning
confidence: 99%
“…Some medical schools started to use videos to demonstrate procedural skills. But students' feedback revealed that using online videos alone was not enough to learn the required clinical skills and they are still in need for faculty teaching [2].…”
Section: Introductionmentioning
confidence: 99%